Discourse Representation of Consumerism in Mobile Telecommunication Television Advertisements - Fredrick Friday John (Randwick International of Education and Linguistics Science Journal, 2020)
Telecommunication advertisements have bifurcating relations, functioning as a buoyant part of the capitalist market, and as instruments indexing consumerism, which bridges the gap between service providers and subscribers. Previous linguistic studies on the subject have focused on speech acts, mainly locutionary and illocutionary acts, and the lexical and stylistic resources in telecommunication advertisements. This study focuses on the representations of consumerism in MTN and GLO advertisements. The study adopts a model labeled as conceptual-textual meaning in advertisements, which annexes the principles of critical stylistics, pragmatic acts, and multimodality to analyse both textual and multimodal excerpts from ten (10) MTN and GLO television advertisements. These were downloaded from youtube, where they are streamed to reach a vast majority of internet users after they had been aired on mainstream television and cable stations. The study reveals that consumerism is the most pivotal feature projected in the advertisements of MTN and GLO. Advertisements and services are principally designed to condition choice of the subscribers to expand their consumptions. Consumerism is metaphorised, using food substances and materials co-opted from the socio-cultural milieus that condition the advertisements. Conceptual-textual functions like naming and describing, enumerating and exemplifying and prioritising, and direct acts, indirect acts, conversation, emotional and psychological acts, as well as the textual resources of inference, metaphor, reference, relevance, and metapragmatic joker are used extensively to show consumerism. The study concludes every service option is aimed at expanding consumerism, while the cost of services, interest, and use of the services are the shades of consumption of telecommunication services